The Akuammiline Alkaloids; Origin and Synthesis - Eckermann, Ruben; Gaich, Tanja (Synthesis, 2013)
Due to their structural diversity, elegant polycyclic molecular architecture, and biological activity, the indole alkaloids have been investigated by organic chemists over the last century. The first akuammiline alkaloid, echitamine, was isolated in 1875 and first described in 1880. Owing to the exceptional structure of akuammiline alkaloids, it was not until 125 years later that the first successful total synthesis was accomplished. This review will give an overview of this class of alkaloids, pinpointing its structural characteristics and showcasing the completed total syntheses. Furthermore, an overview of the structural diversity is given.1 Introduction2 Structural Analysis3 Biosynthesis4 Completed Total Syntheses4.1 (±)-Vincorine4.2 (–)-Vincorine4.3 (±)-Aspidophylline A4.4 (+)-Scholarisine A5 Conclusion
Keywords: alkaloids; biosynthesis; indoles; natural products; polycycles